Educação superior e inclusão: trajetórias de estudantes universitários com deficiência e a intervenção da terapia ocupacional - Nogueira, Lilian de Fatima Zanoni (2019)
Formal education for young people and adults includes their participation in higher education and is a key part of preparing them for the world of work and for facilitating social participation. This thesis investigated school life trajectories of students with disabilities and their experience in higher education. The research on a specific institution, and dialogue with other occupational therapists working in the area, made it possible to recognize facilitators and impediments found in the life paths of students with disabilities. The qualitative, descriptive and exploratory study was developed from interviews with ten students with disabilities from a community education institution, and five interviews with occupational therapists coordinating inclusion programs in Brazilian universities. Content analysis guided the understanding of the interviews. Students' stories, show positive and significant changes in the everyday lives of those who experience higher education, providing careers and experiences that reflect in greater autonomy and independence. The experience of disability is singular, linked with the support people have received throughout their lives and their understanding of disability. Some students have shown they understand disability as an individual process to which they must adapt or be supported by their needs. This fact overloads the student with the need for self-overcoming, and difficult to establish social co-responsibility discussions between the space in the programs and inclusive living of students with disabilities. Both programs and professionals prioritize individual actions indicating that it is necessary to expand collective interventions in the context. Individual interventions and actions such as study support, improved teacher-student communication support, diverse evaluation methods that enhance skills, should be part of the process, but should not be unique with respect to inclusion program. It is considered that occupational therapists, as part of an inclusion program in higher education teams, can and should intervene in institutional dynamics assuming a technical, ethical, aesthetic and political commitment. The intervention should be directly linked in institutional dynamics and support students in their lifestyles, reducing the invisibility of people with disabilities in the educational space and promote their participation in the decision-making processes about the program's institutions. In addition, professional action should also favor collective actions, which include beyond the physical spaces, the communication and the relations between teachers, students, and employees. The care in the educational space should not be confused with a clinical space, and should be directed to incorporate the educational project the need to identify and overcome the suffering of individuals, anticipating the meeting, interaction, collaboration, recognition of singularities and potentialities of each person, which should objectify the happiness of the subjects and the collectives. Recognition of interdependence can be a guideline for the practice of actions that are often focused only on students with disabilities. As the debate on interdependence becomes part of the academic context, the recognition of care / respect for singular actions in relation to each other is facilitated with positive reflexes for all.